The cumulative and residual changes in eccentric knee flexor strength indices following soccer-specific treadmill running: Novel considerations of angle specific torque - Page, R. M.; Greig, M. (Journal of Sports Sciences, 2020)
With potential implications for recovery and conditioning practices, the aim of this study was to assess the cumulative and residual response of angle specific eccentric knee flexor (eccKF) strength indices following soccer-specific activity. Thirteen semi-professional soccer players were therefore required to complete a 90-minute soccer-specific treadmill running. with eccKF isokinetic strength assessments completed pre-trial, immediately post-trial, and 48 hours post-trial. The strength assessments comprised the completion of 5 repetitions at angular velocities of 60 and 300 deg·s-1. Isokinetic data was analysed for measures of peak torque (PT), angle of peak torque (APT), functional range (FR), and angle specific torque (AST). Significant post-trial impairments were observed for measures of slow velocity PT60 (6.6%) and AST300 (12.5%). Further significant differences were observed 48 hours post-trial for PT300 (10.7%) and PT60 (12.8%) PT, APT60 (~15°), and AST300 (>13.6%). These data have implications for post exercise recovery monitoring and the prescription of recovery modalities and conditioning practices in the 2 days following match-play. The AST and APT responses highlight the importance of analysis of the entire strength-angle curve and at a range of angular velocities.